Physical Activity as a Protective Factor Against Depression Incidence and as a Treatment for Depression - Oluszczak, Karolina; Korta, Karolina; Szeliga, Anna; Szostak, Agata; Wawszkowicz, Konrad; Śmigielska-Mikołajczyk, Maria Janina; Dyląg, Liliana; Łowicka, Weronika; Szopińska, Kinga; Graca, Magdalena (Quality in Sport, 2024)
Abstract Introduction: Depression is one of the most common and serious mental health disorders that negatively affects how you feel, think, and act. This syndrome is characterized by stress and emotion dysregulation, involving compromised structural integrity of frontal-limbic networks.It causes persistent feelings of sadness and a lack of interest in activities once enjoyed. Effective treatments, including therapy and medication, are available and can help manage the symptoms and improve quality of life. The aspect of physical activity as a component of depression treatment is currently being intensively studied. Purpose of work: This work provides a review of the knowledge on the relationship between physical activity and depression. Summary: Depression has a profound impact on the personal life, relationships, and work of those affected by the condition. Pharmacological and psychological interventions remain the cornerstone of treatment. However, these treatments do not produce the desired effects in all patients. This article presents the conclusion that physical exercise, as an alternative method for preventing and treating depression, is effective. The recent literature also suggests significant mental health benefits from being physically active, even at levels below the public health recommendations. Therefore, health practitioners should encourage any increase in physical activity to enhance mental health.